Reducing initial loss to follow-up among people with bacteriologically confirmed tuberculosis: LINKEDin, a quasi-experimental study in South Africa - Meehan, Sue-Ann; Hesseling, Anneke C; Boulle, Andrew; Chetty, Jolene; Connell, Lucy; Dlamini-Miti, Nomthandazo J; Dunbar, Rory; Du Preez, Karen; George, Gavin; Hoddinott, Graeme; Jennings, Karen; Marx, Florian; et al. (Open Forum Infectious Diseases, 2024)
Every person diagnosed with tuberculosis (TB) needs to initiate treatment. The World Health Organization estimated that 61% of people who developed TB in 2021 were included in a TB treatment registration system. Initial loss to follow-up (ILTFU) is the loss of persons to care between diagnosis and treatment initiation/registration. LINKEDin, a quasi-experimental study, evaluated the effect of 2 interventions (hospital recording and an alert-and-response patient management intervention) in 6 subdistricts across 3 high-TB burden provinces of South Africa. Using integrated electronic reports, we identified all persons diagnosed with TB (Xpert MTB/RIF positive) in the hospital and at primary health care facilities. We prospectively determined linkage to care at 30 days after TB diagnosis. We calculated the risk of ILTFU during the baseline and intervention periods and the relative risk reduction in ILTFU between these periods. We found a relative reduction in ILTFU of 42.4% (95% CI, 28.5%-53.7%) in KwaZulu Natal (KZN) and 22.3% (95% CI, 13.3%-30.4%) in the Western Cape (WC), with no significant change in Gauteng. In KZN and the WC, the relative reduction in ILTFU appeared greater in subdistricts where the alert-and-response patient management intervention was implemented (KZN: 49.3%; 95% CI, 32.4%-62%; vs 32.2%; 95% CI, 5.4%-51.4%; and WC: 34.2%; 95% CI, 20.9%-45.3%; vs 13.4%; 95% CI, 0.7%-24.4%). We reported a notable reduction in ILTFU in 2 provinces using existing routine health service data and applying a simple intervention to trace and recall those not linked to care. TB programs need to consider ILTFU a priority and develop interventions specific to their context to ensure improved linkage to care.